Microstructure and Mechanical Behaviour of Friction Welded AISI 2205/AISI 1040 Steel Joints - Kirik, Ihsan; Ozdemir, Niyazi; Sarsilmaz, Furkan (Carl Hanser Verlag, 2012)
The goal of this study is to investigate the effect of friction time on mechanical and microstructural properties of dissimilar AISI 1040/AISI 2205 stainless steel couples. The experiments were carried out with continuous drive friction welding set-up. Friction welding experiments with different frictional times and constant friction pressure as well as rotational speed were carried out. The strength of the welds was determined by tensile strength tests. Hardness variation of the joint was also obtained. The results were compared with those of previous studies. The results of applied tests and observations showed that the properties of microstructure change and that the interface temperature increases with friction time. The best tensile strength of the joint was observed for the specimen welded at 1700 rpm rotation speed and a friction time of 3 s.
Keywords: Duplex Stainless-Steel